1973
DOI: 10.1017/s0033291700049631
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism in patients treated with lithium: a review and two case reports

Abstract: SYNOPSISTwo different types of hypothyroidism can occur during lithium administration, one with evidence of underlying thyroiditis, the other without. Two cases are reported, one of type 1, the other of type 2, and 17 other cases of lithium-induced hypothyroidism in the literature are reviewed. The literature on the occurrence of goitre during lithium treatment, and that on the alteration of thyroid function tests are also reviewed. Possible mechanisms for the disturbance of thyroid function are discussed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Our results are compatible with evidence of a direct inhibitory action of lithium on the thyroid gland [Bhattacharya and Wolff, 1976;Bagchi et al, 1978]. Crowe et al [1973] suggested that lithium might induce two types of hypothyroidism, one with thyroiditis, one without. Our results may sup port this hypothesis; lithium acts directly on the thyroid gland, causing an impairment of hormone production and/or release in most patients, whereas a minority of patients, females as a rule [Villeneuve et al, 1974], develop antithyroid antibodies and thyroiditis.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are compatible with evidence of a direct inhibitory action of lithium on the thyroid gland [Bhattacharya and Wolff, 1976;Bagchi et al, 1978]. Crowe et al [1973] suggested that lithium might induce two types of hypothyroidism, one with thyroiditis, one without. Our results may sup port this hypothesis; lithium acts directly on the thyroid gland, causing an impairment of hormone production and/or release in most patients, whereas a minority of patients, females as a rule [Villeneuve et al, 1974], develop antithyroid antibodies and thyroiditis.…”
Section: Discussionsupporting
confidence: 91%
“…A similar iendency towards over-representaiion of hypothyroidism in female patients was been noted during the initial phase of treatment (Fyrö et al 1973;Villeneuve et al 1973) and in two groups of case reports representing altogefher 26 female and 4 male cases of hypoihyroidism (Crowe et al 1973;Lindstedt et al 1973). These 56 females accounted for 19 cases of hypothy¬ roidism, while just one case occurred in the remaining 30 patienis (P < 0.001).…”
supporting
confidence: 64%
“…Most subjects, however, escape from this general action, while some remain hypothyroid as long as treatment is continued (Emerson et al 1973;Fyrö et al 1973). A survey of the case reports including 26 females and 4 males with persistent hypothyroidism suggests that female patients have an increased susceptibility to develop this complication (Crowe et al 1973;Lindstedt et al 1973). A few large-scale, cross-sectional studies have been con¬ ducted using the measurement of serum thyrotrophin (TSH) as a sensitive indicator of hypothyroidism (Emerson et al 1973;Lindstedt et al 1973).…”
mentioning
confidence: 99%
“…For instance, lithiumtreated patients show increased prevalences of goitre (1)(2)(3)(4) and, to a lower extent, increased incidences of clinical hypothyroidism (5,6). Thyroid function tests are modified in lithium-treated patients and volunteers within a few months of treatment (7)(8)(9)(10).…”
mentioning
confidence: 99%